Application of green building technology in industrial new building - Harun, Hasnida; Badrol Hisham, Muhamad Afiq; Anuar, Mohammad Irhamnar; Kabir, Mohd Hafizalrisman (Penerbit UTHM, 2020)
A green building design process begins with an intimate understanding of the construction site including its beauties and complexities. An ecological approach to design which aims to integrate the systems that being introduced with the existing on-site ecological functions. These ecological functions provide habitat, respond to the movements of the sun, purify the air as well as catch, filter and store water. Designers can create features in their buildings that mimic the functions of particular ecosystems. Species that thrive in natural ecosystems may also utilize habitats created in man-made structures. Creating new habitat on structures in urbanized areas is especially important to support biodiversity and a healthy ecosystem...